Ciṭṭhī patrī. - Premacanda, 1881-1936; Amr̥tarāya.; Madan Gopal (Illāhābāda, Haṇsa Prakāśana, 1962)
Letters of a Hindi author.
In Hindi.
Keywords: Premacanda, -- 1881-1936 -- Correspondence; Authors, Hindi -- 20th century -- Correspondence; Premacanda, -- 1881-1936; Authors, Hindi; 1900-1999; Records and correspondence